THE LEGAL POSITION OF CHURCH MARRIAGE FROM THE PERSPECTIVE OF MARRIAGE LAW AND THE CONSTITUTIONAL RIGHTS OF CHRISTIANS IN INDONESIA - Yohanes Payong Keda; Abdul Rokhim; S Roy Hendrayanto; Imron (Sekolah Tinggi Ilmu Hukum Awang Long, 2025)
Marriage in the Christian tradition has undergone a historical development, from a simple community practice in the ancient Roman world, where a personal declaration of commitment between the prospective bride and groom was considered valid, to becoming a sacred and legal institution elevated as a sacrament of the church. The 11th-century Reformation of the Catholic Church and the 16th-century Council of Trent strengthened the sacramental status of marriage, requiring its publication and solemnization before the church community to avoid disputes and ensure legal and theological validity. In Indonesia, the practice of church marriage was influenced by the colonial legal system, which required civil registration in addition to a church blessing. Today, a church blessing is considered to fulfill the spiritual aspect, while registration at the Civil Registry Office is an absolute prerequisite for legal recognition and protection of the constitutional rights of Christian families. This research uses a normative juridical method with a study of regulations, doctrines, and implementation practices. The research results show that there is a dualism of recognition—a valid church marriage may not be legally recognized by the state without civil registration, which has an impact on the legal status, inheritance, and administration of children. Analysis of church legal theory, formal state legality, constitutional rights, and legal certainty emphasizes the importance of harmonization between positive law and the sacred values of the church so that the rights of Christian families are comprehensively protected. The research recommendations emphasize the need for public education, church advocacy, and inclusive state services so that church marriages receive full spiritual and legal recognition in Indonesia.